Pengajaran Bahasa Arab Menggunakan Media Gambar Bergerak Untuk Meningkatkan Penguasaan Kosakata - Mariyatul Qibtiyah; Walfajri Walfajri (Institut Agama Islam Negeri (IAIN) Metro, 2020)
This study aimed to analyze the process of teaching Arabic using moving picture media and the level of vocabulary mastery in Islamic Junior High School. This research method was quantitative with an experimental approach. The research was conducted at Islamic Junior High School Darul Amal Metro, involving 30 students of grade VIII as the sample. The data collection method used a test. The test method was aimed at students to get vocabulary mastery data. The data analysis technique used the T-test to determine the level of vocabulary mastery after using moving picture media. The results showed that the learning process by using moving picture media had been able to increase students' learning activities and enthusiasm. The spirit of learning characterized by a high concentration during the learning process, encouraging students to understand the lesson easily. The high of learning concentration caused by the characteristics of the moving picture media varied and corresponded with students' progress. The success of using moving picture media was supported by the teacher's ability to use media. The results of statistical analysis showed that the application of moving picture media in learning Arabic had a significant effect on students' vocabulary mastery.